PERUBAHAN TRADISI PERMAINAN MERIAM KARBIT DI DESA TANJUNG HARAPAN, KECAMATAN SINGKEP, KABUPATEN LINGGA, PROVINSI KEPULAUANRIAU - Mohamad Imam Handoko; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study, entitled Tradition carbide cannon Games Village Cape of GoodHope, District Singkep, Lingga regency, Riau Islands Province. This study aims todescribe the implementation process of tradition Games carbide cannon, to determinewhat changes occur in Games carbide cannon tradition and to reveal the factorscausing changes in tradition carbide cannon games, as well as describe theparticipants involved in the implementation of Tradition carbide cannon game.To analyze qualitative research data, the collected data is then presenteddescriptively describe or recount the results of research with the description of thelogical sentences in order to understand and easy to understand.This research was conducted in the village of Tanjung Harapan, Singkepdistricts, Lingga regency, Riau Islands Province. The results of the study indicate achange in tradition Games carbide cannon, which nowadays is rarely the person whodid this game. This is due to several factors, including internal and external factors.Among the internal factors, the drive from within the community to change,education and mindset that have been advanced, heterogeneous Pnduduk, a sense ofdissatisfaction, the influence of foreign cultures, contact with other cultures.